The Role of Sheikh Ahmad Khatib Al-Minangkabawi in the Dynamics of Hajj in the Archipelago in the Late 19th and Early 20th Centuries - Syifa Mardhiyah; Abdul Rozaq; Agus Riyadi (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to examine the profound role of Sheikh Ahmad Khatib al-Minangkabawi (1860-1916) in the dynamics of the history and practice of Hajj in Indonesia through a historical perspective and literature analysis. As a great scholar from Minangkabau who was appointed as the Grand Imam of the Shafi'i School of Law at the Grand Mosque, he became a central reform agent who connected the intellectual heritage of the Hijaz with the Indonesian Hajj pilgrims in the late 19th to early 20th centuries. This study uses a descriptive qualitative research approach, with references to historical research and library research. The results of this study are: Sheikh Ahmad Khatib al-Minangkabawi's significant contribution lies in the reform of religious practices brought home by pilgrims, namely by opposing ta'assub mazhab and encouraging the purification of Hajj jurisprudence through an emphasis on the Qur'an and Sunnah. In addition, his strong criticism of traditionalism, especially the matrilineal inheritance system and the Naqsyabandiyah Order and the cadre formation of scholars (including the founders of Muhammadiyah and NU) fundamentally shaped the puritan and modernist identity of Islam in Indonesia. This research is expected to increase understanding of the Hajj as a channel for Islamic intellectual mobility.